Evolution of ransomware. Issue 5 (1st September 2018) - O'Kane, Philip; Sezer, Sakir; Carlin, Domhnall
Abstract : Cybercrime has long since transformed from a world of Maverick attackers to a criminal business. Ransomware is a malware that renders a victim's computer or data unusable and is increasingly being used by criminals to generate revenue through extortion. This study contributes to the authors' knowledge by exploring the transition from the early‐day scams, to extortion implemented by current ransomware. They examine the pathway from the first clumsy ransomware attempts to the present day sophisticated ransomware attack campaigns. This Crypto‐warfare now accounts for estimated damages of 1 billion. Considering the fact that many Internet users appear to be unaware of ransomware and do little to protect themselves, they argue that this low‐impact extortion, using highly automated methods, has proven very rewarding for the criminals. As criminals have been early adopters (or abusers) of Internet technology, they expect that ransomware will continue to evolve beyond the capability of present day defence solutions.